Analisis Kesiapan Karir Mahasiswa Diploma Tata Busana Dalam Persaingan Bisnis Era Digital - Novit, Sri Zulfia Novrita (AI Society & STMIK Indonesia, 2024)
This study aims to measure the career readiness of Diploma in Couture students at the Faculty of Tourism and Hospitality, Padang State University in facing digital business challenges. This research uses a survey method by collecting data from 172 of the total population of students who are academically active in 2024. The sample technique used was purposive sampling. The indicators measured include digital literacy readiness, technology adaptability readiness, practical experience readiness, and modern business skills readiness. The results showed that students' digital literacy readiness was categorized as very low with a score of 46%, technological adaptability readiness was 60%, readiness due to practical experience was 64%, and readiness for a very low understanding of modern business skills was 43%. These findings indicate a significant gap between academic training and current industry requirements, which hinders students from adapting quickly to new technologies and managing fashion businesses effectively in the digital age. This study aims to measure the career readiness of Diploma in Couture students at the Faculty of Tourism and Hospitality, Padang State University in facing digital business challenges. This research uses a survey method by collecting data from 172 of the total population of students who are academically active in 2024. The sample technique used was purposive sampling. The indicators measured include digital literacy readiness, technology adaptability readiness, practical experience readiness, and modern business skills readiness. The results showed that students' digital literacy readiness was categorized as very low with a score of 46%, technological adaptability readiness was 60%, readiness due to practical experience was 64%, and readiness for a very low understanding of modern business skills was 43%. These findings indicate a significant gap between academic training and current industry requirements, which hinders students from adapting quickly to new technologies and managing fashion businesses effectively in the digital age.